2022
DOI: 10.3390/antibiotics11030297
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationships between the Chemical Structure and Antimicrobial Activity of a GAPDH-Related Fish Antimicrobial Peptide and Analogs Thereof

Abstract: The structure–activity relationships and mode of action of synthesized glyceraldehyde-3-phosphate dehydrogenase (GAPDH)-related antimicrobial peptides were investigated. Including the native skipjack tuna GAPDH-related peptide (SJGAP) of 32 amino acid residues (model for the study), 8 different peptide analogs were designed and synthesized to study the impact of net charge, hydrophobicity, amphipathicity, and secondary structure on both antibacterial and antifungal activities. A net positive charge increase, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 93 publications
1
24
0
Order By: Relevance
“…In this study, despite GG3A15 exhibiting the highest helicity, its overall antibacterial activity was slightly lower than that of GG3A7. This observation confirmed that augmenting the helicity of peptides with already favorable helical tendencies had limited on enhancing their activity. ,, More importantly, our investigation highlighted position 7 as a critical determinant of antibacterial activity in short α-helical peptides, which was consistent with analogous studies …”
Section: Discussionsupporting
confidence: 90%
“…In this study, despite GG3A15 exhibiting the highest helicity, its overall antibacterial activity was slightly lower than that of GG3A7. This observation confirmed that augmenting the helicity of peptides with already favorable helical tendencies had limited on enhancing their activity. ,, More importantly, our investigation highlighted position 7 as a critical determinant of antibacterial activity in short α-helical peptides, which was consistent with analogous studies …”
Section: Discussionsupporting
confidence: 90%
“…The hydrophobicity of peptides is also represented by the grand average of hydropathicity index (GRAVY) value, generated from Expassy – ProtParam tool (https://web.expasy.org/protparam/). The positive value of GRAVY shows that peptide is hydrophobic, while a negative value represents hydrophilic [25] . All peptides were categorized as hydrophilic, excluding P4 with a positive GRAVY value of 0.130.…”
Section: Resultsmentioning
confidence: 99%
“…The positive value of GRAVY shows that peptide is hydrophobic, while a negative value represents hydrophilic. [25] All peptides were categorized as hydrophilic, excluding P4 with a positive GRAVY value of 0.130.…”
Section: Physicochemical Properties Of Peptides From Casein Hydrolysa...mentioning
confidence: 99%
“…Interestingly, these three peptide analogs (5, 6, and 7) have demonstrated the ability to permeabilize the cytoplasmic membrane of the Gram-positive bacterium M. luteus, whereas analogs 1 and 8 did not exhibit significant permeabilization in tests involving the same microorganism …”
Section: Discussionmentioning
confidence: 99%
“…The results previously obtained in membrane permeabilization assays, together with the MICs and minimal bactericidal or fungicidal concentrations (MBCs and MFCs), pointed to a mixed mechanism of action in which both membrane permeabilization and intracellular targets seem involved. 42 Recent studies have assessed the antimicrobial activity of these analogs under various physicochemical conditions, quantifying their hemolytic activity, and investigating their digestibility in a dynamic model of human digestion. It was demonstrated that the antimicrobial activity of these peptides was stronger under acidic pH conditions and that it was sensitive to the presence of cations, in particular, divalent cations.…”
Section: Introductionmentioning
confidence: 99%